The role of global health partnerships in shaping policy practices on access to medication in Cameroon: theory, models and policy practices - Ngoasong, Michael Zisuh. (2010)
This thesis argues that health policy practices on access to medication in Cameroon have been shaped by global health partnerships (GHPs), with the result that the capacity of the state has been undermined and the national health system fragmented, with no resultant reduction in the incidence and burden of malaria and HIV I AIDS. GHPs have played an increasing part in relation to access to medication in a number of developing countries in Africa, defined in terms of potential and actual access to pharmaceuticals and healthcare services. GHPs are supposed to provide a better policy response to the practical problem of access to medication by combining the expertise of UN agencies, the pharmaceutical industry, international civil society organizations, national government and local groups to formulate and implement country-specific policies. Ostensibly, they are able to bridge the gap between medical technology and the public health needs of poor societies. Neither of these claims can be substantiated.